2016
DOI: 10.1155/2016/8341617
|View full text |Cite
|
Sign up to set email alerts
|

A Multicriteria Approach for the Optimal Location of Gasoline Stations Being Transformed as Self-Service in Taiwan

Abstract: Location selection significantly influences business success. In particular, location selection for the fuel stations is characterized by constraints on investment in facilities and by criteria that involve a series of social utilities. Recently, a leading fuel company in Taiwan initiated transforming its traditional gas stations into self-service. However, it is difficult to select an existing station to be transformed as self-service because there are many conflicting goals in the problem of location selecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…There is currently a consensus that the business site selection problem is a Multi-Criteria Decision-Making problem (MCDM). Many examples can be found that use this approach to tackle the problem: the selection of a shopping center in Turkey [38], the selection of warehouses for agricultural products [39], the location of gas stations [19,40], the opening of a new supermarket in Spain [41], the selection of Surface Water Treatment [42] or solar energy plants [43], among many others.…”
Section: Related Literaturementioning
confidence: 99%
“…There is currently a consensus that the business site selection problem is a Multi-Criteria Decision-Making problem (MCDM). Many examples can be found that use this approach to tackle the problem: the selection of a shopping center in Turkey [38], the selection of warehouses for agricultural products [39], the location of gas stations [19,40], the opening of a new supermarket in Spain [41], the selection of Surface Water Treatment [42] or solar energy plants [43], among many others.…”
Section: Related Literaturementioning
confidence: 99%
“…It was therefore imperative to use both methods to achieve the desired results. Additionally, previous published studies have also demonstrated the integration of AHP and IPA [15,16], since IPA has only range and does not have average values. Hence, in this condition we have highlighted data distribution in Table 1 and have provided all of the data acquisition questionnaires which will facilitate future research in this field.…”
Section: Introductionmentioning
confidence: 98%
“…Among the various multi-criteria approaches available, the Analytical Hierarchy Process (AHP) and Importance Performance Analysis (IPA) are the most recognized and reliable risk management tools [26]. That's why studies related to gas stations employ these methods frequently [27,28]. The AHP method was proposed by Saaty in 1977.…”
Section: Introductionmentioning
confidence: 99%